Dunas: a framework for deformable bézier surfaces and curves - ALBUQUERQUE, Marco Túlio Caraciolo Ferreira (2008)
Powerful graphics processors on personal computers and game consoles make surface representation a good choice due to their processing capabilities. However, creating surface models still appears to be in the realm of the CAD/CAM and not game development according to Dave Eberly. This work unify both fields, physics and geometry, exploring the interface between geometry and physically based animation by incorporating well established physic models into Bézier surfaces for the simulation of deformable objects. By doing so, we create a simple yet powerful representation of the model, with Bézier Curves and Surfaces, and incorporate some of the most used methods of automated shape changing animation. Our approach makes possible to use real physics simulations in limited platforms, like Desktop Flash and mobile J2ME. At the same time, enables the use of even more complicated scenes on powerful platforms that makes use of dedicated graphics cards like Desktop Personal Computers.